Urgensitas Plea Bargain In The Criminal Justice System In Indonesia - Insan Pribadi; Desi Syamsiah (Bajang Institute, 2026)
Crime in Indonesia continues to increase year after year, a situation that is not commensurate with the capacity of law enforcement officers and the effectiveness of judicial institutions, resulting in a backlog of cases and high costs of law enforcement in Indonesia. One of the stages of the modern criminal justice system to address these issues is the Plea Bargain stage. This is where an agreement is reached between the defendant and the public prosecutor that allows the defendant to plead guilty in exchange for a lighter sentence or demand. This can be both an opportunity and a challenge for all law enforcement officers